The traditional village as a part of a cultural landscape: the development of cultural agriculture tourism in Catur, Bali - I Dewa Gede Agung Diasna Putra; I Made Adhika (Universitas Mercu Buana, 2024)
The Covid-19 pandemic has highlighted the importance of the agriculture sector, which has been abandoned by some people, most notably in certain cultural tourism zones of Bali. Balinese culture, which is inextricably linked to agricultural operations and in which agrarian culture adds its aspects to the community's everyday cultural activities, has enormous potential for future tourism expansion. However, certain resort zones in Bali have abandoned the agricultural sector, threatening food and culture. This occurrence has prompted concerns about whether the tourism economy's agriculture practices can continue to serve their roles. Could agriculture meet Balinese cultural and home needs in this tourism-based economy? In this case, the Balinese engage in agricultural undertakings and offer their agricultural produce to their ancestors and God. Conversely, people worship God by praying for a bountiful harvest with farm products. However, as a community, this agricultural activity has begun to decline, which is expected to limit future efforts to conserve the culture. Through field study and descriptive analysis, this paper seeks to investigate various agricultural and cultural potentials in a rural cultural environment as a tourist attraction while conserving agrarian culture to save the local culture. By juxtaposing agricultural, cultural, and tourism activities in a balanced manner, local communities will benefit not only economically, but also in efforts to preserve local culture.